Friend or foe: the role of platelets in acute lung injury - Yang, Jichun; Zhou, Xun; Qiao, Xinrui; Shi, Meng (Frontiers in Immunology, 2025)
Lung diseases, including acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), are associated with various etiological factors and are characterized by high mortality rates. Current treatment strategies primarily focus on lung-protective ventilation and careful fluid management. Despite over 50 years of basic and clinical research, effective treatment options remain limited, and the search for novel strategies continues. Traditionally, platelets have been viewed primarily as contributors to blood coagulation; however, recent research has revealed their significant role in inflammation and immune regulation. While the relationship between platelet count and ALI/ARDS has remained unclear, emerging studies highlight the “dual role” of platelets in these conditions. On one hand, platelets interact with neutrophils to form neutrophil extracellular traps (NETs), promoting immune thrombosis and exacerbating lung inflammation. On the other hand, platelets also play a protective role by modulating inflammation, promoting regulatory T cell (Treg) activity, and assisting in alveolar macrophage reprogramming. This dual functionality of platelets has important implications for the pathogenesis and resolution of ALI/ARDS. This review examines the multifaceted roles of platelets in ALI/ARDS, focusing on their immunomodulatory effects, the platelet-neutrophil interaction, and the critical involvement of platelet-Treg cell complexes in shaping the inflammatory environment in ALI.